PEMETAAN POTENSI PONDOK PESANTREN SEKITAR KAMPUS BARU UIN PROF. K.H. SAIFUDDIN ZUHRI PURWOKERTO DI PURBALINGGA - Imron Hamzah; Khairunnisa Dwinalida; Asep Amaludin (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This community service project focused on mapping, development, and empowerment of pondok pesantren communities surrounding the new campus of UIN Prof. K.H. Saifuddin Zuhri Purwokerto in Purbalingga Regency. The primary objectives were to identify the potential of local pesantren, strengthen their institutional capacity, and empower the surrounding communities. The program employed a descriptive qualitative approach, utilizing surveys, interviews, and participatory observation methods. The mapping results revealed that pesantren in the area possess significant potential in religious education, community-based economic initiatives, and social empowerment. However, key challenges include limited infrastructure, human resource capacity, and access to digital technology. Development initiatives were directed at improving educational quality through the integration of religious and general sciences, strengthening pesantren infrastructure, and supporting digital transformation. Community empowerment efforts included entrepreneurship training, digital literacy improvement, and pesantren-based creative economy programs. The collaboration among the university, local government, and pesantren proved effective in transforming pesantren into centers of community empowerment. This initiative is expected to foster independent, innovative, and competitive pesantren, while promoting the sustainable welfare of the surrounding communities.